Peningkatan Kapasitas Kader dalam Mewujudkan Masyarakat Bebas DHF (Dengue Haemoragic Fever) di Desa Cemani - Ekan Faozi; Dimas Ria Angga Pribadi; Fadilah Rolavi Jannah; Fatikhah Izzatul Khusna (Pusat Riset dan Inovasi Nasional, 2024)
Dengue hemorrhagic fever (DHF) is an acute infectious disease caused by the dengue virus which is transmitted through the bite of the Aedes aegypti mosquito and enters human blood. Data on DHF sufferers in Dukuh Waringinrejo in RW 20 Gang Elang 2. Information from the village midwife obtained 5 DHF sufferers, 3 children and 2 adults. The purpose of this activity is to find out if there is an increase in the knowledge of posyandu cadres, especially RW 19 and 20 Dukuh Waringinrejo, Cemani Village in preventing DHF through counseling to posyandu cadres. Posyandu Nusa Indah 15 is the location for implementing counseling which is located in Dukuh Waringinrejo. The number of participants in counseling on prevention of DHF was 15 posyandu cadres. The method used in carrying out community service activities is in the form of counseling about DHF with the target of posyandu cadres RW 19 and 20 Dukuh Waringinrejo, Cemani Village. The intervention was carried out using the lecture method and using educational videos about DHF. The activity instrument was in the form of pre-test and post-test questionnaires. From the results of the average pre-test and post-test values, it can be concluded that there is an increase in knowledge of posyandu cadres after counseling is held.